The management of ADHD in children and young people - Harpin, Valerie (Mac Keith Press, 2017)
This book is an accessible and practical guide on all aspects of assessment of children and young people with Attention Deficit Hyperactivity Disorder (ADHD) and how they can be managed successfully. The multi-professional team of authors discusses referral, assessment and diagnosis, psychological management, pharmacological management, and co-existing conditions, as well as ADHD in the school setting. New research on girls with ADHD is also featured. Case scenarios are included that bring these topics to life.